Determinants of Access to Education and ICT in Nigeria - Oluwatayo, Isaac B.; Ojo, Ayodeji O. (Journal of Economics and Behavioral Studies, 2017)
The world where development is driven by advancement in education and Information and Communication Technology (ICT) is fast emerging. This study therefore examined the determinants of access to education and ICT in Nigeria. The study used information from 4,508 households from the National Bureau of Statistics (NBS) General Household Survey (GHS) Data. Probit regression model and descriptive statistical tools were used to analyze relevant data. Analysis of the data showed that average household size was fairly large consisting of 7 members with majority (85.1percent) of the households headed by men. Average age of the household heads was 52 years while average years of education was 4 years. Also, 82.0percent and 61.2percent of the households in urban and rural Nigeria respectively had access to education. Therefore, inequality in access to education exists based on location. The factors influencing access to education in Nigeria were found to include age, gender, marital status and household size. The results also revealed age, years of education, marital status, gender and household size as determinants of access to ICT. Analysis of different ICT devices used in Nigeria showed that Radio (88.1percent), Mobile Phones (86.4percent) and Television (55.1percent) were the most widely used. Meanwhile, a significant difference exist in the factors influencing access to education and ICT in rural and urban Nigeria. The study therefore recommended increased investment in education and infrastructure. Government and private organizations should encourage gender equality in access to ICT through gender sensitive interventions.